Identification of circulating biomarkers in sera of Plasmodium knowlesi-infected malaria patients – comparison against Plasmodium vivax infection - Chen, Yeng (BMC Infect Dis, 2015)
BACKGROUND: Plasmodium knowlesi was identified as the fifth major malaria parasite in humans. It presents severe clinical symptoms and leads to mortality as a result of hyperparasitemia in a short period of time. This study aimed to improve the current understanding of P. knowlesi and identify potential biomarkers for knowlesi malaria. METHODS: In the present study, we have employed two-dimensional gel electrophoresis-coupled immunoblotting techniques and mass spectrometry to identify novel circulating markers in sera from P. knowlesi-infected patients. Specifically, we have compared serum protein profiles from P. knowlesi-infected patients against those of healthy or P. vivax-infected individuals. RESULTS: We identified several immunoreactive proteins in malarial-infected subjects, including alpha-2-HS glycoprotein (AHSG), serotransferrin (TF), complement C3c (C3), hemopexin (HPX), zinc-2-alpha glycoprotein (ZAG1), apolipoprotein A1 (Apo-A1), haptoglobin (HAP), and alpha-1-B-glycoprotein (A1BG). However, only TF and HPX displayed enhanced antigenicity and specificity, suggesting that they might represent valid markers for detecting P. knowlesi infection. Additionally, six P. knowlesi-specific antigens were identified (K15, K16, K28, K29, K30, and K38). Moreover, although HAP antigenicity was observed during P. vivax infection, it was undetectable in P. knowlesi-infected subjects. CONCLUSIONS: We have demonstrated the application of immunoproteomics approach to identify potential candidate biomarkers for knowlesi malaria infection.